Measurements of axial and peripheral anterior chamber depth: accuracy of a photographic method. Issue 3 (March 1984) - Hitchings, R. A.; Romano, J.; Clark, P.
Abstract : The minimum significant (p = 0.05 level) detectable change noted on measuring anterior chamber depth by a photographic method was found to be 7% either way from the mean. The minimum significant change for a peripheral chamber depth 5 mm from the optic axis was found to be 25% either way.